2018
DOI: 10.1007/s12011-018-1472-1
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory Effect of the Supplemented Copper Ion on In Vitro Activity of Bovine Lactoferrin to Murine Splenocytes and RAW264.7 Macrophages

Abstract: Bovine lactoferrin (LF) was supplemented with Cu at three contents of 0.16, 0.32, and 0.64 mg/g LF, respectively. After then, LF and Cu-supplemented LF products were assessed for immuno-modulation in murine splenocytes and RAW264.7 macrophages, using dose levels of 10-40 μg/mL and four evaluation reflectors including stimulation index of splenocytes, T lymphocyte subpopulations, macrophage phagocytosis, and cytokine secretion. The results indicated that LF and Cu-supplemented LF products had suppression on spl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…The immunoregulatory effect of intracellular copper metabolism has been examined in several studies (Videla et al, 2003;Steinborn et al, 2017;Zhao and Zhao, 2019). Deigendesch et al (2018) found that depriving intracellular copper transporters of copper ions inhibited inflammasome activation in macrophages, thereby regulating the immune phenotype of macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The immunoregulatory effect of intracellular copper metabolism has been examined in several studies (Videla et al, 2003;Steinborn et al, 2017;Zhao and Zhao, 2019). Deigendesch et al (2018) found that depriving intracellular copper transporters of copper ions inhibited inflammasome activation in macrophages, thereby regulating the immune phenotype of macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Low-concentration copper preparations have been reported to have promising immunomodulatory potential and to contribute to oxidative stress in macrophages (Videla et al, 2003;Steinborn et al, 2017;Zhao and Zhao, 2019). Mitochondrial-derived reactive oxygen species (mtROS) are believed to derive mainly from NADH dehydrogenase when there is a high NADH/NAD+ ratio in the mitochondrial matrix.…”
Section: High Levels Of Mitochondrial-derived Reactive Oxygen Species Might Enhance Ccm-promoted Expression Of Pdgf-bb By M2a Macrophagesmentioning
confidence: 99%
“…discovered that copper deficiency dramatically reduced the production of superoxide anion in macrophages, which in turn affected the ability to kill yeast, Candida, etc., making the organism more susceptible to infection ( 51 ). However, studies has been demonstrated that excessive copper supplementation can inhibit macrophage function ( 52 ), and so, maintaining copper homeostasis inside and outside the cell is one of the prerequisites for proper macrophage function. While White et al.…”
Section: Relationship Between Copper and Immunitymentioning
confidence: 99%
“…Lactoferrin, which is an 80 kDa iron-binding glycoprotein, is found in cow milk, as well as in most human body fluids, including breast milk, sweat, and vaginal fluid. Several studies have shown that lactoferrin inhibits bacterial [4,5], viral [6,7], and fungal [8] infections, activates immune cells such as natural killer (NK) cells [9] and macrophages [10], and stimulates the proliferation of T cells and B cells. However, the mechanisms by which cow milk modulates immune cell activation remain unknown.…”
Section: Introductionmentioning
confidence: 99%